Olympic movement and cancer prevention - Malchrowicz-Mośko, Ewa; Rozmiarek, Mateusz (Journal of Education, Health and Sport, 2022)
The aim of this article was to discuss the issue of kinesiophobia during and after oncological treatment. It highlights the role of the Olympic movement in the field of health promotion and cancer prevention, as well as the role of athletes who have overcame an oncological disease in promoting an active attitude of society towards sport. The attention was paid also to the insufficient number of sports events targeted at onco-patients.